From Three-Dimensional Cell Culture to Organs-on-Chips - Huh, Dongeun (Trends Cell Biol, 2011)
Three-dimensional (3D) cell culture models have recently garnered great attention because they often promote levels of cell differentiation and tissue organization not possible in conventional two-dimensional (2D) culture systems. Here, we review new advances in 3D culture that leverage microfabrication technologies from the microchip industry and microfluidics approaches to create cell culture microenvironments that both support tissue differentiation and recapitulate the tissue-tissue interfaces, spatiotemporal chemical gradients, and mechanical microenvironments of living organs. These ‘organs-on-chips’ permit study of human physiology in an organ-specific context, enable development of novel in vitro disease models, and could potentially serve as replacements for animals used in drug development and toxin testing.